Training on Installation and Use of Woocomerce in Developing MSME Product Marketing in Palembang City - Fitri Masito; Sukahir Sukahir; Heru Kusdarwanto; Retno S. Wulandari; Parjan Parjan; Yeti Komalasari; Dwi Cahyono; Siti Salbiah Ristumanda; Risa Riana Puspita Sari; Suci Ryski Nur Afriyani; Anda Lusia; Christina Brown (Asosiasi Profesi Multimedia Indonesia, 2023)
Improving the economy and competitiveness of Micro, Small, and Medium Enterprises (MSMEs) is the main focus in regional development, including in the City of Palembang. In the context of globalization and digitalization, e-commerce platforms such as WooCommerce have become a potential tool for expanding the market reach of MSMEs. This activity aims to provide understanding and skills to MSME actors in installing, configuring and managing online stores using WooCommerce as a marketing development tool for MSME products in Palembang City. In this context, the main problem formulation is the extent to which MSME players understand and master WooCommerce, the obstacles they face in using it, and the impact of training on increasing competitiveness, product sales and local economic growth. The methods used in this activity are by using training methods, surveys and data analysis. This activity is expected to help MSMEs utilize the potential of WooCommerce to the maximum. Apart from that, this research also measures the positive effects of training in terms of creating new jobs and regional economic growth. It is hoped that the results of this activity can provide guidance for MSME players and stakeholders in developing the marketing of MSME products in Palembang City through e-commerce platforms. Then the socialization results were published on Poltekbang Palembang social media and community service journals. So, it can be concluded from the results of this activity that all participants are able to create online stores in accordance with the guidelines and can increase sales.